Symbolism of Rain in the Qur'an: Semiotic Analysis Based on Charles S. Peirce's theory - Salsabila, Iffah Fathan (IJoIS: Indonesian Journal of Islamic Studies, 2025)
This study analyzes the symbolism of rain in the Qur'an using the semiotic approach developed by Charles S. Peirce. In the Qur'an, rain is often used as an analogy for various spiritual and moral concepts such as mercy, sustenance, and signs of Allah's power. Peirce's semiotic theory, which involves the triadic concepts—representamen (the sign itself), object (what the sign refers to), and interpretant (the meaning produced in the observer's mind)—is utilized to explore the meaning behind the symbol of rain in Qur'anic texts. This research identifies and interprets various verses mentioning rain to uncover hidden meanings and the contribution of the rain symbol to the overall message of the Qur'an. By focusing on three verses: QS. Al-Furqan: 48-49 (rain as mercy), QS. Asy-Syu’aro: 173 (rain as disaster), and QS. An-Nur: 43 (rain as a natural phenomenon), this study reveals how the Qur'an uses natural symbols to convey spiritual and ethical messages. The results of this analysis are expected to enrich the interpretation of symbolism in sacred literature and demonstrate the relevance of Peirce's semiotic theory in the study of religious texts.